2006
DOI: 10.3732/ajb.93.12.1791
|View full text |Cite
|
Sign up to set email alerts
|

Are differences in breeding mechanisms and fertility among populations contributing to rarity in Grevillea rhizomatosa (Proteaceae)?

Abstract: Plant breeding systems are seldom studied across the breadth of a species' range. For many systems, this precludes an informed assessment of the evolutionary biology of a species, particularly of the factors that shape fecundity. Grevillea rhizomatosa is a threatened species of shrub known only from a 7 × 8 km area and c. 2000 plants in northern New South Wales, Australia. The species reproduces asexually from rhizomatous suckers, and fruit are only produced in a few populations. Over two flowering seasons, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 43 publications
(51 reference statements)
0
16
0
Order By: Relevance
“…Abbott et al 2007). Third, it means that genetic rescue might not be effective in all G. repens populations (c.f., Gross and Caddy 2006) and care needs to be taken to avoid triploid plants when sourcing vegetative and other material from one population for enhancing the size of other populations.…”
Section: Management and Conservation Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abbott et al 2007). Third, it means that genetic rescue might not be effective in all G. repens populations (c.f., Gross and Caddy 2006) and care needs to be taken to avoid triploid plants when sourcing vegetative and other material from one population for enhancing the size of other populations.…”
Section: Management and Conservation Implicationsmentioning
confidence: 99%
“…Plants from this genus play important ecological roles within the Australian biota including the provision of food for numerous vertebrate and invertebrate species (Olde and Marriott 1994) and extinction of populations may have flow-on ecological effects. Many Grevillea species combine both sexual and clonal reproduction (Makinson 2000) however, some populations within these taxa rely predominantly (or exclusively) on vegetative reproduction (Burne et al 2003;Gross and Caddy 2006;Olde and Marriott 1994). Some species appear to currently lack sexual reproduction altogether (Kimpton et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…; Vaughton & Ramsey, 1991) supplemented by within‐flower self‐pollination due to stigma opening at or soon after anthesis before self‐pollen has been removed (e.g. early receptivity in Grevillea rhizomatosa Olde & Marriott; Gross & Caddy, 2006). Other mechanisms that prevent autonomous self‐pollination include a narrowed stigmatic groove at anthesis (Matthews, Gardner & Sedgley, 1999), and complex stigmatic structures blocking the path for self‐pollen to reach the stigmatic groove such as cellular outgrowths (Ladd et al ., 1998).…”
Section: Introductionmentioning
confidence: 99%
“…2004). Moreover, the Australian Proteaceae are thought to have very low levels of self‐compatibility and species are often subject to pollen limitation (Goldingay & Carthew 1998, but see Smith & Gross 2002, Gross & Caddy 2006). Macadamia is the only Australian rain forest Proteaceae studied in detail, but most research effort has focused on cultivars in orchards and usually M. tetraphylla × M. integrifolia hybrids.…”
mentioning
confidence: 99%
“…Studies of non-rainforest Proteaceae have demonstrated that fragmentation, small population size, and low plant density can have negative impacts on reproduction (Lamont et al 1993, Field et al 2005, survival (Drechsler et al 1999), gene mixing and gene flow (Coates & Sokolowski 1992), and genetic diversity (Ayre et al 1994, Llorens et al 2004. Moreover, the Australian Proteaceae are thought to have very low levels of self-compatibility and species are often subject to pollen limitation (Goldingay & Carthew 1998, but see Smith & Gross 2002, Gross & Caddy 2006. Macadamia is the only Australian rain forest Proteaceae studied in detail, but most research effort has focused on cultivars in orchards and usually M. tetraphylla × M. integrifolia hybrids.…”
mentioning
confidence: 99%